PD-1/PD-L1 blockade in HIV-associated advanced lung cancer: from mechanisms to clinical practice - Chen, Ruifang; Ren, Shuai; Tang, Haicheng; Wu, Qingguo (Frontiers in Immunology, 2026)
The advent of antiretroviral therapy (ART) has ushered in a remarkable era of prolonged survival for individuals living with Human Immunodeficiency Virus (HIV). Yet this prolonged survival has paradoxically coincided with an increasing burden of non-AIDS-defining malignancies, particularly advanced non-small cell lung cancer. Targeted inhibitors of the programmed cell death protein-1 (PD-1) pathway and its ligand, programmed death-ligand 1 (PD-L1), have now become the cornerstone of modern immunotherapy. Nevertheless, comprehensive studies evaluating the application of these inhibitors in HIV-positive individuals with concurrent lung cancer remain scarce. This review elucidates the dual mechanism of action of PD-1/PD-L1 inhibitors in this patient population: on one hand, blockade of the PD-1/PD-L1 axis enhances anti-tumor activity in vivo, while on the other, it reverses latent HIV infection and restores immune function. Current evidence suggests that PD-1/PD-L1 inhibitors demonstrate favorable safety and promising efficacy in ART-controlled HIV patients with lung cancer. However, comprehensive clinical trials remain imperative to validate their long-term outcomes, given the existing limitations of small sample sizes and population heterogeneity in current studies. This article seeks to establish a theoretical foundation for tailoring immunotherapy strategies to this unique patient population.